Web application development project - Chua, Jing Xian. (2011)
The objective of this web application development project is to create content for the application and implementing scaffolding mechanism for PRES-on. The content for the application are needed to show how PRES-on works in promoting modeling or in another words system modeling. It also acts as a guide for user to know more about system modeling through the various case studies being created, and also there is a platform available for them to create models. Scaffolding mechanisms are added into PRES-on to enhance the learning process of a user. It provides a form of assistance to the user. The scaffolding mechanisms in PRES-on is in the form of procedural prompts. The prompts are added in to simulate the user’s thinking to make them think in depth while they are creating models in PRES-on. It is also guiding the user making sure they are on the right track.